Short communication. Survey for incidence of Okra mosaic virus in northern Nigeria and evidence for its transmiáion by beetles - Alegbejo, M.=700 1 Ogunlana, M.; Banwo, O.
(Es, En)
Ilus., 17 ref.
Keywords: HIBISCUS ABELMOSCHUS; VIRUS DE LAS PLANTAS; MORBOSIDAD; TRANSMISION DE ENFERMEDADES; ELATERIDAE; ESPAÑA; ESCARABAJOS; SPANISH JOURNAL OF AGRICULTURAL RESEARCH